The level of galectin-3 in the blood serum of patients with chronic hepatitis C - V. A. Kovalevа; N. S. Zhevnerova; T. V. Antonova (Журнал инфектологии)
Aim. to assess galectin-3 level in the serum of HCV patients according to the biochemical activity of hepatitis, liver fibrosis, in view of insulin resistance and overweight.Materials and methods: The content of serum galectin-3 was detected in 78 patients with chronic hepatitis C in age from 20 to 55 years with oligosymptomatic course of the disease and minimally expressed liver fibrosis in most cases. We evaluated the association between the content of galectin-3 in the blood and metabolic disorders, biochemical activity of hepatitis and fibrosis of the liver.Results: In patients with normal ALT levels (42% of the patients), the average level of galectin was 3.17 (1.23; 5.94) ng / ml. Elevated levels of gammaglobulin in blood was noted in 21 patients, 15 of them also had elevated levels of galectin-3. Patients infected with genotype 1b, galectin-3 was higher than other genotypes. With a high viral load (> 500,000 IU / mL), the average level of galectin-3 was higher than the lowest. One-third of patients with overweight levels of galectin-3 was higher than normal. MI was diagnosed in the majority (61.5%) examinees, and in these patients, there was an increase level of galectin-3. When comparing the levels of galectin in patients with varying degrees of fibrosis, significant differences were found only when F0 – F2 (p = 0,033).Conclusion: The galectin-3 serum level was elevated in most patients with chronic hepatitis C. The maximum increase in galectin-3 was observed in patients with severe liver fibrosis (F 3). The connection between the level of galectin-3 and the metabolic syndrome components such as body mass index, and insulin resistance was found.